Purple seed stain of soybean - its incidence, effect on seed quality andintegrated management - P.V. PATIL*, P. SATYA PRASANTH and (Indian Phytopathology, 2007)
The purple seed stain infection among the different seed samples collected from different areas of northern Karnataka was ranged between 2.2 to 7.7 and 0.1 to 14.7 per cent during 2003 and 2004, respectively. There was a significant reduction in test weight, oil and protein content, seed germination and seedling vigour index (SVI) in seeds with 76-100 per cent purple seed coat staining. For integrated management of the disease either carbendazim or carbendazim (12%) + mancozeb (63%) seed treatment @2 g/kg seed along with two foliar applications at 15 days interval starting from the initial pod development stage either with thiophanate methyl or carbendazim @ 0.1 per cent were effective in increasing the plant stand and in reducing the seed infection.